2018
DOI: 10.1111/1744-9987.12662
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Analysis of Coronary Artery Calcification in Dialysis Patients in vivo by Dual‐Energy Computed Tomography Angiography

Abstract: While vascular calcification is an important factor regulating prognosis in dialysis patients, its components have not been adequately studied. We analyzed in vivo components of calcification in the coronary arteries of dialysis patients using the effective atomic number from dual-energy computed tomography. In dialysis patients (hemodialysis, N = 10; peritoneal dialysis, N = 12), average of median effective atomic number was 13.8 in the hemodialysis group, and 13.7 in the peritoneal dialysis group. No signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
1
24
1
Order By: Relevance
“…[15][16][17][18][19][20] Other calcium minerals such as calcium carbonate, calcium pyrophosphate and amorphous calcium phosphate have also been reported, as well as heterogeneous composition between patients. 15,18,21 Thus, it seems that calcium in these lesions is present as a mixture that may contain several non-HAp materials, summarised in Scheme 1B. The role that these non-HAp calcium minerals may have in different stages of CVD, and their potential as imaging biomarkers, remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Other calcium minerals such as calcium carbonate, calcium pyrophosphate and amorphous calcium phosphate have also been reported, as well as heterogeneous composition between patients. 15,18,21 Thus, it seems that calcium in these lesions is present as a mixture that may contain several non-HAp materials, summarised in Scheme 1B. The role that these non-HAp calcium minerals may have in different stages of CVD, and their potential as imaging biomarkers, remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…They often form in the human body, for instance, a major part of the stones in the human urinary system consist of both [1,2]. These minerals also are found in salivary stones and other human pathogenic formations [3][4][5]. Besides, weddellite and whewellite often occur in crustose and foliose lichen thalli on the surface of Ca-bearing rocks and minerals [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Operations in JW have led to greater awareness of blood conservation and advances in blood-free surgeries (1). With the combined use of erythropoietin and self-donated blood preoperatively, or cell salvage and transfusion alternatives intraoperatively, more invasive surgeries than nephrectomy have been performed successfully without blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Nishizawa et al recently reported a study in a paper titled “ Compositional Analysis of Coronary Artery Calcification in Dialysis Patients In Vivo by Dual‐Energy Computed Tomography Angiography ” . We are interested in this article as their finding on calcification in dialysis patients is path breaking.…”
Section: Acknowledgmentsmentioning
confidence: 99%